Dekonstruksi Makna Hifz al-Nasl di Era Kontemporer: Analisis Hukum Keluarga Islam terhadap Pilihan Childfree - Abdul Rahman; Yudi Wahyudin; Mumu Fahmudin; Abdul Kodir Alhamdani; Halmi Abdul Halim (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
The childfree phenomenon the deliberate choice of married couples not to have children is increasingly prevalent in Indonesia and has sparked serious debate in Islamic family law discourse, particularly regarding the principle of hifz al-nasl (preservation of progeny) as one of the fundamental elements of maqashid al-syari'ah. This study aims to deconstruct the meaning of hifz al-nasl from classical and contemporary perspectives, analyze the legal status of the childfree choice within the framework of Islamic family law, and formulate a comprehensive and contextual legal construction. This research employs a normative legal research method using library research, Jasser Auda's contemporary maqashid al-syari'ah approach, conceptual approach, and comparative approach. Data analysis was conducted qualitatively through content analysis, descriptive-analytical, deconstructive-reconstructive, and comparative techniques. The findings reveal three key conclusions: first, the deconstruction of hifz al-nasl produces a more comprehensive understanding through Jasser Auda's reconstruction that expands hifz al-nasl into hifz al-usrah (family protection), shifting the orientation of progeny preservation beyond mere biological reproduction to encompass family quality and overall well-being; second, the typological analysis of childfree yields a graduated legal mapping: voluntarily childfree without valid religious justification is ruled makruh to haram, temporarily childfree is permissible as equivalent to tandzim al-nasl, and voluntarily childfree due to medical emergency may be permitted; third, legal reconstruction based on Jasser Auda's system approach produces a more just and relevant legal construction for Muslim couples in Indonesia. This research contributes to the development of contemporary Islamic family law discourse in Indonesia.